Inactivations of rsbU and sarA by IS256 Represent Novel Mechanisms of Biofilm Phenotypic Variation in Staphylococcus epidermidis - Conlon, Kevin M. (American Society for Microbiology, 2004)
Expression of ica operon-mediated biofilm formation in Staphylococcus epidermidis RP62A is subject to phase variable regulation. Reversible transposition of IS256 into icaADBC or downregulation of icaADBC expression are two important mechanisms of biofilm phenotypic variation. Interestingly, the presence of IS256 was generally associated with a more rapid rate of phenotypic variation, suggesting that IS256 insertions outside the ica locus may affect ica transcription. Consistent with this, we identified variants with diminished ica expression, which were associated with IS256 insertions in the σ(B) activator rsbU or sarA. Biofilm development and ica expression were activated only by ethanol and not NaCl in rsbU::IS256 insertion variants, which were present in ∼11% of all variants. σ(B) activity was impaired in rsbU::IS256 variants, as evidenced by reduced expression of the σ(B)-regulated genes asp23, csb9, and rsbV. Moreover, expression of sarA, which is σ(B) regulated, and SarA-regulated RNAIII were also suppressed. A biofilm-forming phenotype was restored to rsbU::IS256 variants only after repeated passage and was not associated with IS256 excision from rsbU. Only one sarA::IS256 insertion mutant was identified among 43 biofilm-negative variants. Both NaCl and ethanol-activated ica expression in this sarA::IS256 variant, but only ethanol increased biofilm development. Unlike rsbU::IS256 variants, reversion of the sarA::IS256 variant to a biofilm-positive phenotype was accompanied by precise excision of IS256 from sarA and restoration of normal ica expression. These data identify new roles for IS256 in ica and biofilm phenotypic variation and demonstrate the capacity of this element to influence the global regulation of transcription in S. epidermidis.